EFFECT OF POLYETHYLENE GLYCOL-6000 ON CHEMICAL COMPOSITION AND DEGRADABILITY OF WHITE GRAPE POMACE IN BUFFALOES - R. Pirmohammadi; O. Hamidi; A. Golgasemgarebagh; S. Cheraghiyan (Journal of Animal and Plant Sciences, 2012)
An experiment was carried out to study the effect of Polyethylene Glycol 6000 (PEG-6000) inclusion on chemical composition and degradability of dry matter (DM) and crude Protein (CP) of white grape pomace (WGP) in buffaloes. WGP contains some antinutritional factors such as tannins that may cause to decrease its feeding values. Some tanninification agents like Polyethylene glycol (PEG) can enhance the feeding value of tanniniferous feeds. PEG inclusion was done at 4 levels. The nylon bag technique was used to determine the rate of degradability of DM and CP with 3 rumen-fistulated Azeri buffalos. Results showed that DM content of white grape pomace (WGP) decreased with PEG addition. PEG addition was cause to decrease total tannins and total phenols of WGP. According to observations a fraction (rapidly degraded fraction) of DM content of WGP increased between treatments significantly (P<0.05). Also effective degradability (ED) of CP content of WGP decreased significantly (P<0.05). Different tannins in various plant samples may vary not only in total content but also in their ability to affect degradation, and to bind to proteins or fiber. Totally degradability results showed that PEG addition increased DM degradability values and enhanced soluble proteins of WGP.
Keywords: Azeri buffaloes; white grape pomace; polyethylene glycol 6000; degradability